Three Critical COVID-19 Cases Treated with Mesenchymal Stem Cells: A Case Series Report - ZC, Karakoc; D, Koyuncu Irmak; S, Tugrul; F, Ece; CA, Gormeli; K, Ozyilmaz; E, Karaoz (Archives of Clinical and Medical Case Reports, 2021)
This paper reports three critically ill patients diagnosed COVID-19 infection who were treated with conventional therapy and MSCs add-on therapy in combined treatment protocols on a patient centric manner. We followed up and evaluated the cases specifically for efficacy and safety indicators. We introduce promising efficacy and safety data of the add on MSC therapy in COVID-19. We believe that the MSC therapy could be a safe effective therapy method for novel coronavirus as add-on therapy and when applied to the critically ill COVID-19 cases on a personalized approach.